Diathēkē kainē New Covenant as Jewish Apocalypticism in Hebrews 8 - Vandergriff, Kenneth A. (2017)
The Epistle to the Hebrews has been viewed predominantly through a Middle Platonic lens. The new covenant in Hebrews 8 has been viewed as a Platonic polemic against Judaism and a supersessionist text for Christianity. When viewed through a Jewish apocalyptic lens, however, Hebrews 8 stands less as a polemic against Judaism or a supersessionist text for Christianity than as a hope for people going through suffering and oppression. Moreover, an apocalyptic reading of Jeremiah 31 in its original context provides part of the background through which an apocalyptic reading of Hebrews 8 is made possible. To that end, I argue for a reading of Hebrews 8 through a Jewish apocalyptic lens and an understanding of the new covenant that coheres with such a reading.
Keywords: Jeremia -- Prophet; Bibel; Neuer Bund; Apokalyptik; Jüdische Literatur; Frühchristentum; diathēkē; APOCALYPTIC literature (Jewish literature); Apocalypticism; Bible. Hebrews; Bible. Jeremiah; Christianity; Hebrews; Jeremiah; Jews; Judaism; Middle Platonism; New Covenant